2010
DOI: 10.1136/jnnp.2009.183863
|View full text |Cite
|
Sign up to set email alerts
|

What determines quality of life in inclusion body myositis?

Abstract: The functional disability caused by IBM reduces QoL, but psychosocial factors such as mood affect QoL directly and by influencing the degree to which disease severity reduces QoL. Further study should follow the effects of IBM on QoL over time and look at the influence of other psychosocial factors. Such studies may point to psychosocial interventions that may help improve QoL in IBM even if the disease itself cannot be treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(103 citation statements)
references
References 13 publications
9
91
3
Order By: Relevance
“…As in previous studies (Graham et al, 2014;Rose et al, 2012;Sadjadi et al, 2010), in cross-sectional analyses illness perceptions explained large proportions of variance.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As in previous studies (Graham et al, 2014;Rose et al, 2012;Sadjadi et al, 2010), in cross-sectional analyses illness perceptions explained large proportions of variance.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, illness perceptions were included in the analysis; these are beliefs about the time-course of the health threat, its consequences and if it can be cured or controlled, amongst a range of other beliefs (Petrie & Weinman, 2012). Crosssectional studies demonstrate that they explain between 5% and 37% of the variance in quality of life, and 25% of the variance in mood in this context (Graham et al, 2014;Sadjadi, Rose, & Group, 2010). Therefore, we investigated the cross-sectional and prospective influence of PF (experiential avoidance, cognitive fusion and valued living) on life satisfaction and mood over the effects of disability level, and illness perceptions.…”
Section: The Present Studymentioning
confidence: 99%
“…Both reported poorer QoL in the more functionally impaired group on at least one QoL domain, but with no significant differences in emotional functioning [16,28]. Seven studies [7,9,13,15,21,24,25] assessed associations between measures of function and QoL; all reported strong and/or significant associations between physical domains and function. Of these seven, two studies [24,25] reported significant correlations of weak to moderate strength between function and SIP psychosocial.…”
Section: Disease Severitymentioning
confidence: 99%
“…All 12 studies which compared people with MD to healthy controls reported poorer scores for the MD groups on one or more QoL domains [6,7,9,13,[15][16][17][18][19][20][21][22], with five of these studies reporting significantly lower QoL across all sub-scales of the QoL measure [6,7,15,21,22].…”
Section: Qol In MD Compared To Healthy Populationsmentioning
confidence: 99%
See 1 more Smart Citation